1972
DOI: 10.1039/c3972000472a
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactones as kinetic products in the iodolactonization reaction

Abstract: P-Lactones are the kinetic products from the iodolactonization of certain by-unsaturated acids. These y-iodo-p-lactones are readily isomerized to more stable p-iodoy-lactones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1974
1974
2007
2007

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…On the other hand, the preparation of β-lactones is very interesting and depends on reaction conditions. In contrast with butenoic acid that produces only β-lactones [28,61], the intramolecular coiodination of α ,αdimethylbutenoic acid, in small reaction time, produces βlactones, and, in longer reaction time, γ-lactones exclusively [62]. In fact, the propionolactone rearranges under the reaction conditions into the thermodinamically more stable butyrolactone.…”
Section: Intramolecular Coiodination Of Unsaturated Acids and Derivatmentioning
confidence: 99%
“…On the other hand, the preparation of β-lactones is very interesting and depends on reaction conditions. In contrast with butenoic acid that produces only β-lactones [28,61], the intramolecular coiodination of α ,αdimethylbutenoic acid, in small reaction time, produces βlactones, and, in longer reaction time, γ-lactones exclusively [62]. In fact, the propionolactone rearranges under the reaction conditions into the thermodinamically more stable butyrolactone.…”
Section: Intramolecular Coiodination Of Unsaturated Acids and Derivatmentioning
confidence: 99%
“…Irradiation of formanilides caused quantitative decarbonylation, yielding the free anilino derivatives [45].…”
Section: Miscellaneousmentioning
confidence: 99%
“…29 In agreement with this, Barnett and others have shown that in the halolactonisation of salts of b,c-unsaturated acids the products formed under kinetic control are b-lactones arising from ring opening of the halonium ion in an exo manner. [33][34][35] Direct scission of the halonium ion derived from a salt of an a,b-unsaturated monocarboxylic acid to give a b-lactone in one step 36 has been recognised as an unfavourable pathway and achieved only under certain conditions, 19,37-41 vindicating the original view of Tarbell and Bartlett. 22 There are many examples of the rearrangement of cyclic halonium ions to form other three-membered rings.…”
Section: Introductionmentioning
confidence: 99%